Sports mega-events in Brazil: an account of the Brazilian government's actions - Alberto Reinaldo Reppold Filho; Cassia Damiani; Patrícia Silveira Fontana (Karolinum Press, 2018)
During the period from 2007 to 2016, Brazil hosted a number of major sporting events, including the 2014 FIFA World Cup and the Rio 2016 Olympics. The planning and organization of these sporting events, from the bidding process to the monitoring of the legacy, required a great involvement of the Brazilian government. The purpose of this study is to present an account and an assessment of the Brazilian government's actions in relation to these events. The research involved an analysis of government documents in particular those produced by the Ministry of Sport. The results indicated that, apart from the implementation of a policy to promote sport in the country and achieve high-level results in international competition, the engagement of the Brazilian government in such sports mega-events was part of a broad policy focused on international relations, urban change and economic and social development.